Dynamical solvent effects on the charge and reactivity of Ceria-Supported Pt Nanoclusters - Szabová, Lucie (2018)
Supported Pt nanoparticles are key components in heterogeneous catalysis for energy and environment applications that involve vapor and wet conditions. In the latter case, the reaction proceeds at the catalyst-water interface where the solvent actively participates in the reaction mechanism. In this work, ab initio molecular dynamics simulations shed light on the effects of solvation on the reactivity and electronic properties of Pt6 nanocatalysts supported by ceria (CeO2), a highly reducible oxide. The calculated trajectories show that H2O molecules spontaneously dissociate at both the supported Pt6 cluster and at the ceria surface already at T = 350 K. Water dissociation leads to hydroxylation of the ceria surface and, most importantly, to the selective decoration of the metal-oxide periphery with hydroxide ions, which are stabilized by solvent-induced electronic effects and which quickly diffuse to the interfacial Pt sites via Grotthus-like proton chains. The periphery of the metal-oxide interface is thus identified as the active region of ceria-supported Pt clusters in wet environments. Solvation is shown to drive dynamic charge transfers across the metal/oxide interface that modify the cluster charge, a key parameter of the catalyst reactivity.